Integrasi Pengajaran Grammar Dengan An Inspiring Song & Game-Based Lesson For Young Learners Bagi Siswa Kelas 5 SD Supriyadi Semarang - Ririn Ambarini S.Pd., M.Hum.; Anggarani Wilujeng S.S., M.Hum. (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2012)
Teaching English to young learners especially for elementary school students will be different from teaching high school students. The activities of teaching English for young learners in Elementary Schools should be based on the teaching of English that is fun and exciting for young learners. Moreover in giving the English activities, an English teacher should not five the explanation of gramm in the form of formula, sentence pattern or even language rules that have to be memorized by students. Grammar should be taught to the students integrated with vocabularies in the form of statements; for example, Grammar can be taught in the form of communicative questions directly given to the students. So it will be more useful if students experience the language than learn it. Songs and games can be integrated in teaching Grammar to young learners and those are kinds of teaching media that can be used to enhance students’ understanding on the language and learning the English language. This research is an action research that undergoes two cicles. In the first cycle, it was found that the average score of the students when they were taught grammar that was dominated by the use of LKS books is 72.06. It means the percentage of stundents’ capability in learning grammar is 70%. And in the second cycle, it was found that the score of the students in learning grammar that was already integrated with songs and games is 89.81. it means that the percentage of the students’ ability in mastering grammar is 80%. It can be concluded that teaching grammar that is integrated with songs and games is very effective to make the young learners interested in learning English without being realized that they are still learning. In this case, the English teachers should be active enough in choosing the songs that are adjusted with the needs of the students. Key words: teaching, grammar, games, songs, young learners, creative, communicative.